Understanding farmers' valuation of agricultural insurance: Evidence from Viet Nam - Michael King; Anuj Pratap Singh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We employ a novel approach to investigate the reasons for a low demand for agricultural insurance. We confirm that farmers systematically undervalue agricultural insurance. First, we find that private transfers, mainly from family members, explain under-valuation of agricultural insurance. Second, membership of a farmer's union, interpreted as a form of social capital or pro-active behaviour, explains the differential between willingness to pay (WTP) and the predicted economic value of insurance. Third, we help answer the puzzle why the most risk averse are least likely to take up agricultural insurance. We find that over-confidence holds a positive and significant relationship with WTP for agricultural insurance and interpret this as evidence that, within the context of implementation challenges and likely concerns about insurer viability, only the most confident are likely to purchase insurance. These results hold across a range of robustness checks.
Keywords: D81; D91; D84; G22; O13; Q14; 330; Insurance; agriculture; risk; expected utility theory; willingness to pay